Quantum communication systems based on polarization encoded Qubits - Ramos, Mariana Ferreira (2022)
We are now facing a second quantum revolution, that started in the early 21st century, bringing significant technological advances to science, industry and society based on advances on quantum information. The eminent emergence of a quantum computer has boosted concerns about the security of current classical public-key cryptography systems. One important topic in the research field of quantum information is the way we distribute keys in order to allow secure communication between distant parties. QKD systems are already in a pre-commercial stage attracting companies and government heavy investment in researching for quantum information technologies. However, there still are a lot of research to be done in this field, specially regarding high rate transmission, achievable distance reach, and obviously the practical implementation cost. In this thesis, we start by experimentally implement a polarization-encoded discrete variables based quantum communication system which allowed us to identify issues that must be solved in order to make it suitable for QKD protocols practical implementation. In this way, we propose a non-intrusive heuristic method to automatically compensate polarization random drift in standard opticalfiber channels due birefringence effects, and that induces errors during qubit transmission. The compensation of polarization drifts induced by the quantum channel is fundamental to enable the deployment of polarization encoded single-photons transmission over the current optical fiber networks. Furthermore, in this thesis we also propose and validated though numerical simulations a novel polarization-based DV-QKD system that combines the use of phase-modulators for state of polarization (SOP) generation and basis switching with a polarization diversity coherent detection scheme. This enables a full implementation of DV-QKD systems using only classical hardware, which low the cost of QKD systems based on polarization encoded single-photons at the same time that increases the transmission rate. Our results open the door to very high baud-rate polarization qubits transmission in access and metro networks. We report continuous qubit transmission, even in environments subjected to high polarization drift, without consuming extra-bandwidth with a maximum Quantum Bit Error Rate (QBER) of 2%.